Analysis Of Factors Causing Forest and Land Fire in Pulang Pisau Regency, Central Kalimantan - Bambang Hero Saharjo; Uswatun Hasanah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Forest fire is one of the environmental problems that often occurs and is considered important so that it becomes a local and global concern. Forest and land fires are an event that often occurs in Indonesian territory, especially on the island of Kalimantan. Climate is one of the natural factors that can support the occurrence of forest fires, because climatic conditions can affect the dryness of surface fuels. The purpose of this study was to analyze the relationship between hotspots and rainfall on forest fires in Pulang Pisau, Central Kalimantan in the 2017-2021 period. The data used in this study are hotspots using the Terra/Aqua-MODIS (Moderate Resolution Imaging Spectroradiometer) satellite, administrative area data, and rainfall data. The results showed that the highest rainfall was in March of 393 mm/month and the lowest in September was 70 mm/month. High and low rainfall can indicate hotspots which are one of the factors causing forest and land fires. The highest number of hotspots in Pulang Pisau during the 2017-2021 period occurred in 2019 with 3,424 points and the lowest in 2020 with 2 hotspots. This indicates an increase and decrease in rainfall related to the large number of hotspots. Keywords: rainfall, hotspots, fires, Pulang Pisau, Central Kalimantan